Monitoring of damage to skeletal muscle tissues caused by ischemia - Schäfer, Michael; Schlegel, Christian; Kirlum, Hans-Joachim; Gersing, Eberhard; Gebhard, Martha-Maria (Bioelectrochemistry and bioenergetics, 1998)
In medicine, for example during a transplantation, there is a great interest in noninvasive working methods for measuring organ states under the influence of ischemia. Electrical impedance spectroscopy measurements in the frequency range of 100 Hz to 10 MHz were performed on ischemic skeletal muscle tissues of rabbits at 5°C. The measured alterations of the electrical properties of the ischemic skeletal muscles were explained with the help of a suitably extended model. Besides the known effects of edema and changes in conductivity of the intra- and extracellular medium for ischemic organs in general, the model for skeletal muscle has to be extended by the consideration of the membrane resistance. Between 300-850 min the real part of the macroscopical electrical impedance of skeletal muscle decreases during ischemia at frequencies below 1 kHz. This effect is explained by the model as a result of the reduction of the membrane resistance caused by the opening of membrane channels. If further investigations would show a correlation between the transition from reversible to irreversible damage on the one hand, and the opening of membrane channels caused by ischemia on the other hand, then electrical impedance spectroscopy would be a noninvasive, easily applicable method to measure the skeletal muscle state during ischemia.